Fitness coordinators' and fitness instructors' perspectives on implementing a task-oriented community exercise program within a healthcare-recreation partnership for people with balance and mobility limitations: a qualitative study. Issue 19 (10th September 2020) - Skrastins, Olivia; Tsotsos, Stephanie; Aqeel, Hammad; Qiang, Anthony; Renton, Jessica; Howe, Jo-Anne; Tee, Alda; Moller, Jason; Salbach, Nancy M.
Abstract: Background: Healthcare organizations are partnering with recreation organizations to support the delivery of community-based exercise programs for people with balance and mobility limitations. The value and impact of support strategies provided by healthcare organizations, however, have not been examined. Objective: Study objectives were to explore fitness coordinators' and fitness instructors' experiences with implementing a task-oriented community-based exercise program for people with balance and mobility limitations within the context of a healthcare-recreation partnership. Methods: A qualitative descriptive study was conducted. Fitness coordinators and instructors involved with delivering a licensed, group, task-oriented community-based exercise program for people with balance and mobility limitations supported by a healthcare-recreation partnership were interviewed by telephone. Interviews were audio-recorded and transcribed verbatim. A thematic analysis was performed. Results: Eight fitness coordinators and 8 fitness instructors from 14 recreation centres were interviewed. Findings showed that healthcare-recreation partnerships help to optimize exercise program quality and safety through multiple strategies. Fitness coordinators and instructors still face challenges with program implementation at start-up and over time. Recommendations to address these challenges included increased training content related to adjusting exercises to accommodate participant abilities, 1–2 visits from a healthcare professional each program after initial program implementation, suggestions to increase exercise variety, and ongoing education. Conclusions: Findings clarify the role of healthcare organizations, ongoing challenges, and directions for improvement in this program delivery model. Implications for rehabilitation: Community recreation centres can provide task-oriented exercise programs to help people with balance and mobility limitations safely engage in regular exercise Healthcare organizations should provide specific supports to help increase the safety and quality of task-oriented exercise programs in recreation centres Supports include providing clear exercise guidelines, and a healthcare professional who trains fitness instructors, visits the program, answers questions between visits, promotes collaboration and information exchange between recreation centres, and provides ongoing education